The wheat LLM-domain-containing transcription factor TaGATA1 positively modulates host immune response to Rhizoctonia cerealis. (19th September 2019) - Liu, Xin; Zhu, Xiuliang; Wei, Xuening; Lu, Chungui; Shen, Fangdi; Zhang, Xuewen; Zhang, Zengyan
Abstract : A wheat LLM-domain-containing B-GATA transcription factor positively regulates the host immune response to the important pathogen Rhizoctonia cerealis . Abstract: Wheat ( Triticum aestivum ) is essential for global food security. Rhizoctonia cerealis is the causal pathogen of sharp eyespot, an important disease of wheat. GATA proteins in model plants have been implicated in growth and development; however, little is known about their roles in immunity. Here, we report a defence role for a wheat LLM-domain-containing B-GATA transcription factor, TaGATA1, against R. cerealis infection and explore the underlying mechanism. Through transcriptomic analysis, TaGATA1 was identified to be more highly expressed in resistant wheat genotypes than in susceptible wheat genotypes. TaGATA1 was located on chromosome 3B and had two homoeologous genes on chromosomes 3A and 3D. TaGATA1 was found to be localized in the nucleus, possessed transcriptional activation activity, and bound to GATA-core cis -elements. TaGATA1 overexpression significantly enhanced resistance of transgenic wheat to R. cerealis, whereas silencing of TaGATA1 suppressed the resistance. Quantitative reverse transcription–PCR and ChIP–qPCR results indicated that TaGATA1 directly bound to and activated certain defence genes in host immune response to R. cerealis . Collectively, TaGATA1 positively regulates immune responses to R. cerealis through activating expression of defence genes in wheat. This study reveals a new function of plant GATAs in immunity and provides a candidate gene for improving crop resistance to R. cerealis .